Sustainability in the environmental impact assessment and ecological inputs for quarry activities in Melaka Tengah, Melaka - Rahimah Wahid (Tanjong Malim, 2019)
Sustainability in the environmental impact assessment and ecological inputs for quarry activities in Melaka Tengah, Melaka by Rahimah Wahid